Burnout Syndrome in Teachers of Health Sciences in Chachapoyas - Coronel-Zubiate , Franz Tito; Oblitas Pereyra, Olenka María; Silva Díaz , Yshoner Antonio; Pizarro Salazar , Oscar; Zuta Rojas , Jeanile (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The research sought to determine the prevalence of Burnout Syndrome in health teachers at a university in north-eastern Peru. The universe was made up of 69 teachers, and 41 responded to the self-administered instrument called Maslach Burnout Inventory. The results show that 14.6% present this syndrome. The highest indicator was personal fulfillment, while depersonalization and emotional exhaustion were low. According to gender, in both it was similar. According to age group, it had a greater effect in ages between 36 and 51 years. Marital status was more prevalent in singles. We conclude that the prevalence of Burnout Syndrome was low.